Treatment Using Haram Substances According to an Islamic Legal Perspective - Zaleha, Zaleha; Muhammad Amin, Muzakir; Ismail, Diauddin (Journal of Mujaddid Nusantara, 2024)
In terms of the medical field, it has evolved in tandem with human capabilities and the passage of time. Humans, like all other living things, will inevitably suffer from a variety of illnesses, some minor and others serious. People are encouraged to look for other treatment options in an attempt to overcome this illness, and as a result, it is discovered that the law of treatment—which stipulates which treatments are permitted and which are haram—is connected to the usage of haram products and chemicals. Al-Baqarah verses 168 and 172 provide justification for the use of halal and good food, despite the commandment to abstain from haram items. In deciding how to regard haram items, scholars of the mujtahid school also cite QS Al-Baqarah verse 173. This provider makes use of socialization methods and questions and answers in the studio at...., it is hoped that the studio group will be able to know the law of treatment with haram goods/substances in accordance with the Shari'a specified in Islamic law.